Kedudukan Fahaman Ahli Sunnah Wal Jamaah (ASWJ) di Malaysia Pada Abad ke-21M - Azman, Md Zain (2022)
The doctrine of Ahli Sunnah Wal Jamaah (ASWJ) is the basis of Islam as the federal religion of Malaysia. This doctrine has permeated the religious life of the Malaysian Muslim community for decades. However, in the 21st century, there is a growing debate concerning an array of issues of the doctrine, such as the various ideological representations in understanding the ASWJ itself. There is also a view that this doctrine is not central to the development of Islam in Malaysia. The doctrine also faces various challenges both internationally and domestically. This certainly calls a comprehensive study to unravel the aforementioned issues in ways to uphold ASWJ as the dominant Islamic doctrine in Malaysia. The study generally examines the position of Islam in Malaysia based on the ASWJ doctrine. In particular, the study aims to elucidate the concept of the ASWJ ideology among the Muslim community and describe its development in Malaysia. The study also seeks to analyse various challenges and solutions faced by this doctrine in Malaysia. This study is of qualitative orientation. It encompasses the data collection procedures of document analysis, interviews, and observations. The collected data were subsequently analyzed using Inductive-generative method and Nvivo 11 software. The results show that the ASWJ ideological thinking is dominated by the Khalaf and Salafi sects. Despite having differences in methodology, the goal remains similar, to uphold the religion of Islam. The study also found that the success of the ASWJ doctrine was underpinned by the educational and administrative initiatives which have been the backbone of the development of this doctrine since the beginning of the emergence of Islam in Malaysia. Furthermore, the doctrine also has always managed to curb the impending challenges through various responses as fatwa gazetted, law enforcement and book writing by engaging a variety of associated parties. Based on the findings of this study, the position of ASWJ ideology in Malaysia in the 21st century will remain relevant and continue to prosper given that the management of its pillars of thought, institutional development and challenges are kept in order.